Analysis the Role of Housing Fund on the Construction for New Housing Case Study: Diwaniyah governorate / Iraq - et.al, Mays Gheyath Majeed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of housing in Iraq is the big housing need, which causing an increase of informal houses and the rise of housing densities. The Housing Fund is one of the main sources of housing financing in Iraq, by providing loans to citizens to obtain new houses through construction. The fund grants the highest loan limit of 40 million I.D. to the governorate center, 35 million for the kadhaa center and Nahiya center). The aim of the research is to identify analyze the effect of related variable on the size of the loan, such as the plot area, area of construction, the cost of construction, plot price, borrowers' income, and the speculative value of the property. Stratified random sample drown of three towns, and appropriate statistical tests used to analyze. The research concluded that there is no need to make a difference in the upper size of the loan between the three towns, because there is no significant difference in the speculative value of the property, so the research concluded that the value of the loan size does not cover the current cost of construction, and the borrowers income is insufficient to repay the loan. A set of proposals were developed to solve the research problem.